Strategy for Development of Potential Sectors in the Least Developed Regions (Case Study of Sintang District) - Adven Panutan, Fransiskus Aswil; Rustam, Rinaldi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze and review the Potential Sector Development Strategy of the Least Developed Region of Sintang Regency, West Kalimantan Indonesia. The analysis method used in this research is Location Quotient (LQ) & Shift Share analysis. The data used are Gross Regional Domestic Product (GRDP) and Infrastructure Conditions and Supporting Facilities in 2018-2022. The results of the Location Quotient (LQ) calculation in Sintang Regency show that those included in the base sector are Agriculture, Forestry and Fisheries, Mining and Quarrying, Construction, Wholesale and Retail Trade; Car and Motorcycle Repair, Information and Communication, Financial Services and Insurance, Real Estate, Corporate Services, Educational Services and Health Services and Social Activities. Meanwhile, the non-base sectors are the Processing Industry, Electricity and Gas Procurement, Water Procurement, Waste Management, Waste and Recycling, Transportation and Warehousing, Accommodation and Drinking Food Provision, Government Administration, Defense and Compulsory Social Security and other Services. The results of the Shift Share Analysis show that the potential sectors that can be developed are Agriculture, Forestry and Fisheries, Mining and Quarrying, Construction, Wholesale and Retail Trade, Wholesale and Retail Trade: Car and Motorcycle Repair, Information and Communication, Financial and Insurance Services, Real Estate, Corporate Services, Educational and Health Services and Social Activities. These ten sectors have a positive influence so that they can be developed and can increase economic growth in Sintang Regency. In addition, the sustainable development process can be carried out in a good way if the leading sectors of the 17 sectors in Sintang Regency are known.